2020
DOI: 10.1093/jhuman/huaa041
|View full text |Cite
|
Sign up to set email alerts
|

Legal Reasoning for Legitimation of Child Marriage in West Java: Accommodation of Local Norms at Islamic Courts and the Paradox of Child Protection

Abstract: This article discusses challenges posed by the implementation of international human rights law through the case of child marriage in Indonesia. Supporting data consist mostly of court decisions and interviews with judges carried out at three separate Islamic courts in West Java. Results show that the Indonesian pluralistic legal system is structurally organized so as to accommodate human rights norms with religious concerns and customary practices, which therefore provides judges with significant leeway in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several studies show that zinah (extra-and pre-marital sexual intercourse) is a significant contributor to child marriages in Indonesia. For instance, in West Java, parents go to Islamic court to ask for marriage dispensation (legalization of marriage below the legal marriageable age, currently 16 for girls and 19 for boys) to marry their young children, in order to avoid zinah (Horii, 2020). ethnographic research in a village in West Java by grijns et al (2016) confirmed that the key element in most child marriage cases is fear of committing a conceptual framework consisting three elements-modernity, normative systems, and agency.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several studies show that zinah (extra-and pre-marital sexual intercourse) is a significant contributor to child marriages in Indonesia. For instance, in West Java, parents go to Islamic court to ask for marriage dispensation (legalization of marriage below the legal marriageable age, currently 16 for girls and 19 for boys) to marry their young children, in order to avoid zinah (Horii, 2020). ethnographic research in a village in West Java by grijns et al (2016) confirmed that the key element in most child marriage cases is fear of committing a conceptual framework consisting three elements-modernity, normative systems, and agency.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Indonesia which is a country with a majority of Muslims, premarital sexual relations are prohibited and considered as a Zina (sexual relations without legally married bonds) (Horii, 2020). The consequences of premarital sex are family stigma and social sanctions stating that disgrace that has an impact on the fear of teenagers choosing to abandon or even kill their newborn babies (Wong, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The first aspect discusses legal provisions of child marriages normatively in terms of Islamic, national, and international law (Hasibuan, 2019;Sudantra & Laksana, 2019;Ullah et al, 2021: Ahonsi et al, 2019Akter et al, 2022;John, Edmeades, & Murithi, 2019;John, Edmeades, Murithi, et al, 2019;Kohno et al, 2019;McDougal et al, 2020;Melnikas et al, 2020;Raj et al, 2020;Rumble et al al., 2018). The other aspect revolves around child marriage laws in practice, policies, and local culture of marriage (Grijns & Horii, 2018;Horii, 2020;Musawar et al, 2022;Rahiem, 2021;Rumekti & Pinasti, 2016;Supraptiningsih & Hariyanto, 2019;Supriyadi & Suriyati, 2022;Wantu et al, 2021). Nevertheless, the study of child marriages that includes studies of formal legal law and the practice of child marriages in Indonesia as well as their problems regarding the Islamic legal system in Indonesia has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%